Computational Insights Into the Mechanism of Action of Bleomycin as Anticancer and Antibacterial Agent-Via Molecular Docking and Molecular Dynamics - Er, Alev; Çelik, Sefa; Özel, Ayşen E.; AKYÜZ, SEVİM (Wiley, 2025)
Bleomycin (BLM) is the first-line clinical antibiotic used in the treatment of cancer. It inhibits DNA metabolism and is used in conjunction with other anticancer medications to treat various kinds of malignant tumors. This work focuses on examining more fully the bioactivity of BLM as both anticancer and antibacterial agents. Due to the structure-function relationship, the conformational study of the molecule was carried out first, and its potential conformations were identified. Afterwards, using the energy minimization feature of the YASARA structure program, the obtained lowest energy conformation of the molecule and the receptor taken from the protein databank (ligand-free) were optimized. BLM was subjected to molecular docking tests with two antibiotic-binding proteins (PDB IDs: 1ewj and 2zw7) to determine its action mechanism as a TN5 transposon inhibitor. Moreover, its binding affinities towards thymidylate kinase (TMK) (PDB ID: 4qgg) Escherichia coli DNA gyrase B (PDB ID: 6f86) were also evaluated to reveal its antibacterial potential. Additionally, ligand-receptor interactions were assessed via molecular dynamics (MD) process to confirm the stability of BLM docked into antibiotic binding protein (1ewj), TMK (4qgg) and E. coli DNA gyrase B (6f86) within 500 ns (for 1ewj and 6f86) or 200 ns of time (for 4qgg). Molecular mechanics/Poisson-Boltzmann Surface Area methods (MM/PBSA) were used to compute the binding energies through MD simulations. Dynamics cross correlation matrices (DCCM) analysis and principal component analysis (PCA) on the MD data were performed. Results have cleared the mechanism of action of BLM having anticancer and antibacterial properties.
Keywords: Bleomycin; Conformational Analysis; Molecular Docking; Molecular Dynamics